Final report of a phase 2 clinical trial of lenalidomide monotherapy for patients with T‐cell lymphoma. Issue 5 (29th October 2014) - Toumishey, Ethan; Prasad, Angeli; Dueck, Greg; Chua, Neil; Finch, Daygen; Johnston, James; van der Jagt, Richard; Stewart, Doug; White, Darrell; Belch, Andrew; Reiman, Tony
<x xml:space="preserve">Abstract</x> BACKGROUND Patients with T‐cell lymphomas face a poorer prognosis compared with patients with B‐cell lymphomas. New therapeutic approaches need to be developed to improve outcomes for these patients. METHODS Forty patients with recurrent and refractory T‐cell lymphomas other than mycosis fungoides and patients with untreated T‐cell lymphoma who were not candidates for combination chemotherapy were prescribed oral lenalidomide at a dose of 25 mg daily on days 1 to 21 of each 28‐day cycle, with standardized dose reductions for toxicity. The primary endpoint was overall response rate (ORR), and secondary endpoints were complete and partial response rates, progression‐free survival (PFS), overall survival (OS), and safety. The authors also determined duration of response (DoR). RESULTS A total of 40 patients were enrolled in the current study; 1 patient was subsequently deemed ineligible. The ORR was 10 of 39 patients (26%); 3 patients (8%) achieved complete responses and 7 patients achieved partial responses. Three patients had stable disease for ≥5 cycles. The median OS was 12 months (range <1 month to ≥69 months), the median PFS was 4 months (range, <1 month to ≥50 months), and the median DoR was 13 months (range 2 months to ≥37 months), including 5 responses that lasted >1 year. Toxicity was in keeping with the known safety profile of lenalidomide. Among the patients who had recurrent/refractory peripheral T‐cell lymphoma (29 patients), the ORR was 24%, the median OS was 12 months, the median PFS was 4 months, and the median DoR was 5 months (range, 2 months to ≥37 months). CONCLUSIONS In the current study, the use of oral lenalidomide monotherapy demonstrated clinically relevant efficacy among patients with systemic T‐cell lymphomas. It appears to have excellent potential as an agent in combination therapy for patients with T‐cell lymphoma. Cancer 2015;121:716–723. © 2014 American Cancer Society.